2016
DOI: 10.5539/gjhs.v8n12p133
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Eye Assessment of Refractive Surgery Candidates in the Southeast of Iran

Abstract: Anterior segment eye parameters are essential factors in diagnosis, screening and management of abnormal ocular conditions. Based on the previous studies, they might differ from one race or population to another. Sistan-and-Baluchestan province, the southeast of Iran, has special weather conditions and race, plus lack of research on these diagnostic factors. Hence, the objective of the present study was to assess anterior segment parameters using pentacam in this area. 800 eyes of subjects which had been refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Some studies have reported thinnest CCT measurements in myopes, 71,72 whereas others have reported thinnest measurements in emmetropes. 70,73 This lack of agreement and variation may be explained by the use of different methods to determine and subsequently classify refractive error, which compounds the comparison of results across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported thinnest CCT measurements in myopes, 71,72 whereas others have reported thinnest measurements in emmetropes. 70,73 This lack of agreement and variation may be explained by the use of different methods to determine and subsequently classify refractive error, which compounds the comparison of results across studies.…”
Section: Discussionmentioning
confidence: 99%